2018
DOI: 10.3390/su10124622
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Transit-Oriented Development (TOD), Land Use Catchment Areas, and Local Environmental Transformation

Abstract: Transit-oriented development (TOD) has been recognised as a sustainable planning approach and that is typically designed for a whole city. Individual land use characteristics and the causations have often been ignored. Therefore, the primary objective of this study was to explore the factors that influence the land use catchment area (LCA) characteristics at a station neighborhood level. First, it contributes a methodology to measure the LCA by introducing a new concept. The density gradient was introduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We have carried out the Mann-Kendall (MK) trend significance test to study the vegetation characteristics through NDVI and climatic factors in Xinjiang (Tong et al, 2018). The MK test, proposed by Kendall and Mann, is a non-parametric test that does not require the data to be normally distributed and has low sensitivity to outliers in the time series (Xiong, Kim & Qiu, 2019).…”
Section: Theil-sen Median Analysis and Mann-kendall Testmentioning
confidence: 99%
“…We have carried out the Mann-Kendall (MK) trend significance test to study the vegetation characteristics through NDVI and climatic factors in Xinjiang (Tong et al, 2018). The MK test, proposed by Kendall and Mann, is a non-parametric test that does not require the data to be normally distributed and has low sensitivity to outliers in the time series (Xiong, Kim & Qiu, 2019).…”
Section: Theil-sen Median Analysis and Mann-kendall Testmentioning
confidence: 99%
“…Therefore, different layers of urban density and population concentration are created. Tong et al (2018) suggested that TOD in central stations serving as regional centers with more public transport connections had significant impacts on gathering people to live within a defined walking proximity than suburban and neighborhood settlements. However, more suburban and neighborhood TOD should be provided in the planned peri-urban areas when planners expect to deconcentrate urban population from the city (Higgins and Kanaroglou, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, a large and growing body of literature suggests that the built environment in this process experiences a series of positive improvements (Lai, Wang, and Lok 2017). The deterioration of the built environment is often accompanied by low-quality housing or commercial and industrial buildings (Sousa 2006), underutilized, insufficient and abandoned facilities (Lee and Mohai 2012), congested traffic (Tong et al 2018). To tackle with these problems, urban redevelopment can be used to create orderly, comfortable and safe built environment consisting of standard housing with legal property rights and higher quality (Mizuuchi and Jeon 2010), multiple types of infrastructure (Williams et al 2019), recreational facilities (Atkinson, Tallon, and Williams 2019), and accessible transportation (Semenza 2003).…”
Section: Critical Reviewmentioning
confidence: 99%